2017
DOI: 10.1016/j.kint.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

B- and T-cell subpopulations in patients with severe idiopathic membranous nephropathy may predict an early response to rituximab

Abstract: Primary membranous nephropathy (PMN) is characterized by antibodies to the podocyte, but little is known about B- and T-cell populations and their response to rituximab is controversial. To help resolve this we compared 33 lymphocyte subpopulations and 27 cytokines/chemokines in 25 patients with severe PMN and 27 age-matched healthy individuals. At baseline, patients had a significantly increased percentage of naive B-cells with significantly decreased switched and non-switched memory B-cells. There was a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
86
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 47 publications
12
86
1
1
Order By: Relevance
“…As the technology evolves, flow cytometry is becoming an ever more powerful tool for the study of the immune system. A recent study using patients enrolled in the GEMRITUX trial showed that patients had lower proportions of IgD− and IgD+ memory B cells, T Regs and a higher proportion of naïve B cells at baseline compared to healthy donors [71]. In this study by Rosenzwajg et al, patients who responded to treatment were observed to have a lower proportion of T Regs at baseline compared to those who did not respond to treatment.…”
Section: Loss Of Tolerancementioning
confidence: 61%
“…As the technology evolves, flow cytometry is becoming an ever more powerful tool for the study of the immune system. A recent study using patients enrolled in the GEMRITUX trial showed that patients had lower proportions of IgD− and IgD+ memory B cells, T Regs and a higher proportion of naïve B cells at baseline compared to healthy donors [71]. In this study by Rosenzwajg et al, patients who responded to treatment were observed to have a lower proportion of T Regs at baseline compared to those who did not respond to treatment.…”
Section: Loss Of Tolerancementioning
confidence: 61%
“…However, we did not have further research on why CSA treatment of IMN was unresponsive. CsA does not prevent continuing autoantibody formation, production and deposition of IgG4 in the glomeruli may promote the development of MN, 16 but still need larger samples, a long-term follow-up to confirm.…”
Section: R E T R a C T E Dmentioning
confidence: 97%
“…After rituximab monoclonal antibody therapy, peripheral Treg% is elevated, which is intimately correlated with clinical efficacy. 6 Nevertheless, existence of Th17/Treg imbalance in IMN patients, its correlation with the progression and clinical prognosis of IMN patients has not yet been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Univariate COX regression analysis showed that positive renal PLA2R antigen was risk factor for not achieving sponta- 64 41 27 12 10 6 3 3 1 13 13 12 4 3 3 3 3 3 3 1 Log-rank p=0.012 F I G U R E 3 Kaplan-Meier analysis of spontaneous remission in patients with positive and negative phospholipase A2 receptor (PLA2R) antigen deposit. The numbers of at-risk patients at selected time points (3,6,9,12,15,18,21,24,27 and 30 months) were indicated below the plot. Log-rank method was used to evaluate the significance of differences serum albumin and proteinuria, positive renal PLA2R antigen was still an independent risk factor for not achieving spontaneous remission in IMN patients (HR: 2.927; 95% CI: 1.270 to 6.743; P = .012) ( Table 3).…”
Section: Association Between Renal Pla2r Antigen and Spontaneous Rementioning
confidence: 99%